2020 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2020.pr.kepple
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogy training for the development of GTA mindsets and inclusive teaching practices

Abstract: The Physics and Astronomy Department at a large, diverse, master's-granting university has recently implemented a pedagogy training course for graduate teaching assistants (GTAs). Using survey and interview testimonies from GTAs and other lab instructors over the course of three semesters, we identify potential areas of growth that can result from taking the pedagogy course. These areas include: developing a growth mindset and asset-based thinking, identifying the need for inclusive teaching practices, and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…During their time in the course, PMs also read the book "How Learning Works" by Ambrose et al (2010). Indeed, it has been shown that GTAs who attended a similar pedagogy seminar all had something to gain from it despite having different teaching personas (Kepple et al 2020).…”
Section: 3: Pedagogy Seminarmentioning
confidence: 99%
See 1 more Smart Citation
“…During their time in the course, PMs also read the book "How Learning Works" by Ambrose et al (2010). Indeed, it has been shown that GTAs who attended a similar pedagogy seminar all had something to gain from it despite having different teaching personas (Kepple et al 2020).…”
Section: 3: Pedagogy Seminarmentioning
confidence: 99%
“…Practices centered on justice, equity, diversity, and inclusion (JEDI) are explicitly integrated from the first day and throughout the course by coving topics like stereotype threat, imposter syndrome, institutional sexism/racism in STEM, an asset-based framework/growth mindset, and specific techniques for creating an inclusive environment and increasing students' sense of belonging (e.g. Kepple et al 2020). PMs also learn specific pedagogical techniques for eliciting students' ideas, encouraging sensemaking, engaging students in targeted practice and feedback, and helping students become selfdirected learners.…”
Section: 3: Pedagogy Seminarmentioning
confidence: 99%